Imposto inflacionário e transferências inflacionárias no Mercosul e nos Estados Unidos - Cysne, Rubens Penha; Coimbra-Lisboa, Paulo C. (Estudos Econômicos (São Paulo), 2007)
This work presents the series of inflation tax (II), inflation transfers to the comercial banks (TI) and total inflation transfers (TIT=II+TI) of the Mercosul countries and of the United States between 1989 and 2003.